Criminal governance and systems of parallel justice: practice and implications in Brazilian urban peripheries - Ferreira, Marcos Alan (International journal of law, crime and justice, 2022)
This article analyzes the practice and implications of criminal governance through the effective exercise of a system of parallel justice. It is examined the case of the Brazilian gang Primeiro Comando da Capital (PCC), which since 1993 has evolved its scope moving from a powerful prison gang to a complex organization directed to drug trafficking, also having solid governance capacities in deprived urban areas. To examine PCC's judicial function of governance, our methodology is grounded in data triangulation, combining the analysis of documents from the Public Prosecutor's Office of São Paulo state (Brazil), interviews, and literature review. The research confirms empirically earlier conceptual developments on judicial criminal governance by showing a sophisticated parallel justice system by PCC that is operational in three ways. First, PCC manages a trial and punishment system in spaces under their control. Also the gang conducts mechanisms of dispute resolutions for the civilians under their control. Lastly, judicial governance support debt collection and contract enforcement activities. Furthermore, the article innovates by detailing that PCC's judicial function has different purposes depending on the group's hegemony in a given social space, impacting the conditions of peace or violence in these places.